Community pharmacists' perceptions towards online health information in Kuala Lumpur, Malaysia - Ong SW; Hassali MA; Saleem F. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objective: The current study was carried out to assess community pharmacists' perceptions towards online health information, to examine the type of information seek from Internet and to identify the barriers when they retrieved online health information. Methods: The study was designed as a cross-sectional questionnaire-based survey whereby all (300) community pharmacists practicing in Federal Territory of Kuala Lumpur, Malaysia were targeted for data collection. A 35-itemed questionnaire was posted out along with a stamped addressed envelope, invitation letter and support letter. Responses were also accepted via online response. Both descriptive and inferential statistics were used for data analysis. All statistical analysis was performed using SPSS v. 20.0. Results: A total of 67 responses were received with a response rate of 22.3%. The top three frequently health information searched by respondents were medicine information, general healthcare information and disease-related information. High number of respondents agreed that Internet had too much health information to scan through. Gender (p=0.018) showed significant association with visiting established health websites. Meanwhile, statistical significant was observed between age and searching medicine information (p=0.037), undertaking online continuing professional development (p=0.023), as well as searching clinical guidelines (p=0.047). Respondents' education level showed significant association with uncertainty about the reliability of online health information (p=0.023) and unsure about filtering the information (p=0.007). Conclusions: Majority of the respondents expressed positive perception with the use of Internet for health information. The findings of the current study showed the widely use of Internet for health information among community pharmacists. Hence, this study provides opportunity for future works to further examine community pharmacist's retrieval and appraisal skills for online health information, as well as application of this information into their daily pharmacy practice.